1995
DOI: 10.1177/0093854895022004004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of General and Violent Recidivism among Mentally Disordered Inmates

Abstract: One hundred and twenty male inmates who had been released from a maximum-security inpatient psychiatric unit of a federal penitentiary were followed for an average of 92 months. Seventy-eight percent of the sample were arrested for any offense, and 50% were arrested for a violent offense. An actuarial instrument developed using Nuffield's (1982) method correlated .43 with violent recidivism, resulting in 32% relative improvement over chance. The predictors of violent recidivism in this instrument were the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 11 publications
1
15
1
Order By: Relevance
“…Axis I diagnoses) were more than five times as likely to report engaging in violent behaviors (in the previous year) as those without serious mental illness (see Monahan, 1996). In contrast, an attempt to predict general and violent recidivism among parolees from a maximum-security inpatient psychiatric unit showed that psychotic parolees were less likely than nonpsychotic (but also mentally ill) parolees to be rearrested for any offense, and equally likely to be rearrested for a violent offense (Villenueve & Quinsey, 1995). Similarly, Hodgins and Cote (1993) found that the criminal careers of mentally disordered and non-mentally disordered offenders differed little.…”
mentioning
confidence: 98%
“…Axis I diagnoses) were more than five times as likely to report engaging in violent behaviors (in the previous year) as those without serious mental illness (see Monahan, 1996). In contrast, an attempt to predict general and violent recidivism among parolees from a maximum-security inpatient psychiatric unit showed that psychotic parolees were less likely than nonpsychotic (but also mentally ill) parolees to be rearrested for any offense, and equally likely to be rearrested for a violent offense (Villenueve & Quinsey, 1995). Similarly, Hodgins and Cote (1993) found that the criminal careers of mentally disordered and non-mentally disordered offenders differed little.…”
mentioning
confidence: 98%
“…Substance abuse has also been found to demonstrate a strong effect on violent behavior (Pihl and Peterson, 1993;Swanson, 1994). More broadly, the probability of violent recidivism rises with what may be termed Unstable Lifestyle, including, for example, inconsistent work histories (Motiuk and Brown, 1996;Villeneuve and Quinsey, 1995) and difficulties maintaining relationships (Wright and Wright, 1992). In a similar vein, offenders who have failed on conditional release or have a History of Parole/Probation Noncompliance (Dempster and Hart, 2002;Schwaner, 2000;Harris et al, 1993) also present a greater risk of violent recidivism.…”
Section: Research Methodology Instrumentationmentioning
confidence: 99%
“…Total scores are subgrouped into nine levels of probability of violent recidivism within 7 and 10-year periods. The VRAG has been shown to be reliable and valid with mentally disordered offenders (Harris et al, 1993;Quinsey et al, 1998;Villeneuve & Quinsey, 1995) and nonmentally disordered offenders (Barbaree, Seto, Langton, & Peacock, 2001;Glover, Nicholson, Hemmati, Bernfeld, & Quinsey, 2002;Kroner & Loza, 2001;Loza & Dhaliwal, 1997;Loza & Loza-Fanous, 2001;Rice & Harris, 1992). …”
Section: Methodsmentioning
confidence: 99%